Conversion of spent coffee grounds into vermicompost - Hanc, Ales; Hrebeckova, Tereza; Grasserova, Alena; Cajthaml, Tomas (Bioresource technology, 2021)
The present study was focused on vermicomposting of spent coffee grounds (SCG) and its mixtures with straw pellets. The process was evaluated in terms of biological and physico-chemical properties. The greatest number and biomass of earthworms was found in the treatment with 25% vol. SCG + 75% vol. straw pellets. In this treatment, the upper youngest layer exhibited 1.6-fold and 4.5-fold greater earthworm number and biomass, respectively, than the bottom oldest layer. Earthworm weight decreased in direct proportion to the layer age. The oldest treatment layer was characterized by lesser contents of fungi and six hydrolytic enzymes, compared to the younger layers. Further, the oldest treatment layer had suitable agrochemical properties. Earthworms were able to substantially reduce the caffeine stimulant content, which is considered the most representative pharmaceutically active compound.
Keywords: káva; Straw pellets; Coffee; Vermicomposting; Eisenia andrei; Spent coffee grounds; Caffeine; kompostování; Composting